Transparent by choice: Proactive disclosures increase compliance with digital defaults - Paunov, Yavor; Vogel, Tobias; Ingendahl, Moritz; Wänke, Michaela (Frontiers in Psychology, 2022)
Default nudges successfully guide choices across multiple domains. Online use cases for defaults range from promoting sustainable purchases to inducing acceptance of behavior tracking scripts, or “cookies”. However, many view defaults as unethical due to the covert ways in which they influence behavior. Hence, opt-outs and other digital decision aids are progressively being regulated in an attempt to make them more transparent. The current practice of transparency boils down to saturating the decision environment with convoluted legal information. This approach might be informed by researchers, who hypothesized that nudges could become less effective once they are clearly laid out: People can retaliate against influence attempts if they are aware of them. A recent line of research has shown that such concerns are unfounded when the default-setters proactively discloses the purpose of the intervention. Yet, it remained unclear whether the effect persists when defaults reflect the current practice of such mandated transparency boils down to the inclusion of information disclosures, containing convoluted legal information. In two empirical studies (N=364), respondents clearly differentiated proactive from mandated transparency. Moreover, they choose the default option significantly more often when the transparency disclosure was voluntary, rather than mandated. Policy implications and future research directions are discussed.